Pteridophyte Species in The Forest Ecosystem of Lemor Botanical Garden, East Lombok - Muhrani, Zuhra; Jufri, A. Wahab; Wirajagad, Gde Cahyadi (Jurnal Biologi Tropis, 2025)
Indonesia is renowned for having some of the highest biodiversity levels in the world, which includes a wide variety of fern species (Pteridophyta). This study aims to identify and describe the fern species found in the Lemor Botanical Forest Area, East Lombok. The research used a descriptive-exploratory method with a cruise method approach, allowing direct observation and sampling in the field. The results showed a total of 9 fern families belonging to 20 species, with 50 individual plants recorded. The dominant family found was Pteridaceae, comprising 5 species. The species diversity was analyzed using the Shannon-Wiener diversity index, which yielded a value of 2.86, indicating a moderate level of species diversity. These findings demonstrate the ecological potential of the Lemor Botanical Forest Area in supporting the sustainability of fern species, and provide important baseline data for future biodiversity conservation and management efforts in tropical forest ecosystems.  In conclusion, in the Lemor Botanical Garden Forest area of East Lombok, 9 families of ferns have been identified.